Enhancing Marketing Performance of SMEs through Competitive Advantage - Graciafernandy, Maria Augustine; Usriyono, Eko; Istiyawari, Laurene (Proceeding International Conference on Religion, Science and Education, 2024)
This research aims to investigate the influence of competitive advantage as an intervening variable in the relationship between innovative products, digital marketing, and marketing performance on micro, small and medium-sized enterprises (MSMEs) in Semarang. The study addresses the existing gap in understanding the impact of the product innovation-marketing performance relationship. This research was conducted by distributing research questionnaires to 152 small and medium-sized enterprises (MSMEs). The data obtained from the questionnaire responses will be processed using a quantitative approach employing the Structural Equation Modeling (SEM) tool AMOS for analysis. The study reveals that there is no impact on the relationship between digital marketing and competitive advantage. Furthermore, it concludes that both digital marketing and product innovation have no significant impact on marketing performance. However, it is found that the product innovation variable influences competitive advantage, and the competitive advantage variable influences marketing performance. The empirical findings have substantial implications for the marketing and product development strategies of MSMEs in Semarang. The results encourage MSMEs owners to prioritize the development of innovative products for sustainable competitive advantages and heightened market competitiveness. Managing competitive advantage is identified as integral to the overall marketing strategy, providing valuable strategic insights for MSMEs in Semarang to enhance their market position through the effective integration of product innovation, digital marketing, and competitive advantage.